Comparison of knowledge, attitude and practices among student TKP3201 (no mentor) and TKP4203 (with mentor) in Universiti Putra Malaysia - Dzulkarnain, Mohd Hilmi Azfar (2018)
A statistics had stated that the students’ in Malaysia comprising of about 60% of its general population needs to be translated into being the nation’s human capital. It is whether through formal, non-formal, and informal learning approaches. The media also had reported that the students’ performance in Malaysia University had decreased to a low level, which come to worries. Mentoring has been proved in many studies to facilitate positive development effectively. The question now is that whether the extent mentoring and its practices contribute to students learning, and will it influence learning outcomes or not. So, the main problem in this study is that the students seems hard to meet their lecturer because of time constraints which they need to cope with assignments, tests and quizzes. Besides that, students’ lack of focus and attention during lectures in class is also the factor that this study should be looking at. Therefore, objectives for this study are (1) to determine the level of knowledge, attitude, practices and student performance among student TKP3201 (no mentor); (2) To determine level of knowledge, attitude, practices and student performance among student TKP4203 (with mentor); and (3) To compare level of knowledge, attitude, practices and student performance between student TKP3201 (no mentor) with TKP4203 (with mentor). 109 students participated as respondents which respectively consist of 42 students from TKP3201 and 67 students from TKP4203. Quantitative method uses questionnaire design using a Likert scale. SPSS 23 and t-tests analysis were used for data analysis. The performance of students agriculture extension showed that they have significantly different for mean of affective while for mean cognitive and psychomotor there are no significant different in extension programs planning between classes of TKP3201 (no mentor) and TKP4203 (have mentor), in UPM.